2002
DOI: 10.1086/342387
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Epidemiology of Bat‐Associated Cryptic Cases of Rabies in Humans in the United States

Abstract: In the United States, during the past half-century, the number of humans to die of rabies dramatically decreased to an average of 1-2 per year. Although the number of deaths is low, most deaths occur because individuals are unaware that they had been exposed to and infected with rabies virus, and, therefore, they do not seek effective postexposure treatment. Molecular epidemiological studies have linked most of these cryptic rabies exposures to rabies virus variants associated with insectivorous bats. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 44 publications
3
151
0
9
Order By: Relevance
“…Although humans in the United States rarely are infected with rabies virus from any source, 28 of 31 cases of human rabies acquired in (Krebs et al, 2004). Most of these cases (17/24 cases during1990-2000) were related to a specific variant found in silver-haired bats (Lasionycteris noctivagans) and eastern pipistrelles (Pipistrellus subflavus; Messenger et al, 2002;Mondul et al, 2003). Rabid bats of all species were most likely detected in autumn, but L. noctivagans and P. subflavus were more likely to be rabid if collected in summer (Mondul et al, 2003 c References unless otherwise indicated: Alberta (Rosatte, 1985), Arizona (Dean et al, 1960), Arkansas (Heidt et al, 1991), British Columbia (Pybus, 1986), Colorado (Pape et al, 1999), Florida (Bigler et al, 1975), Georgia (Richardson et al, 1966), Illinois (Burnett, 1989), Indiana (Whitaker and Miller, 1973), Kansas (Birney and Rising, 1967), Manitoba (Beauregard, 1969), Michigan (Kurta, 1979), Minnesota (Steece et al, 1982), New York (Childs et al, 1994), Oklahoma (Caire, 1998), Ontario (Beauregard, 1969), Pennsylvania (Wampler and Kirkland, 1981), Saskatchewan (Pybus, 1986), South Carolina (Parker et al, 1999), Texas (Rohde et al, 2004).…”
Section: Most Cases Of Rabies In the Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…Although humans in the United States rarely are infected with rabies virus from any source, 28 of 31 cases of human rabies acquired in (Krebs et al, 2004). Most of these cases (17/24 cases during1990-2000) were related to a specific variant found in silver-haired bats (Lasionycteris noctivagans) and eastern pipistrelles (Pipistrellus subflavus; Messenger et al, 2002;Mondul et al, 2003). Rabid bats of all species were most likely detected in autumn, but L. noctivagans and P. subflavus were more likely to be rabid if collected in summer (Mondul et al, 2003 c References unless otherwise indicated: Alberta (Rosatte, 1985), Arizona (Dean et al, 1960), Arkansas (Heidt et al, 1991), British Columbia (Pybus, 1986), Colorado (Pape et al, 1999), Florida (Bigler et al, 1975), Georgia (Richardson et al, 1966), Illinois (Burnett, 1989), Indiana (Whitaker and Miller, 1973), Kansas (Birney and Rising, 1967), Manitoba (Beauregard, 1969), Michigan (Kurta, 1979), Minnesota (Steece et al, 1982), New York (Childs et al, 1994), Oklahoma (Caire, 1998), Ontario (Beauregard, 1969), Pennsylvania (Wampler and Kirkland, 1981), Saskatchewan (Pybus, 1986), South Carolina (Parker et al, 1999), Texas (Rohde et al, 2004).…”
Section: Most Cases Of Rabies In the Unitedmentioning
confidence: 99%
“…Bat bites were reported in only one FIGURE 2. Monthly distribution of submissions of bats and number of bats that tested positive for rabies virus in Alabama, 1995Alabama, -2005 of 22 cases of human rabies from 1981-98 where the virus variant was linked to bats (Krebs et al, 2000;Messenger et al, 2002). This variant of rabies virus might be able to replicate in epidermal tissue at a lower temperature, allowing minute amounts of virus associated with a scratch or bite to become established in a human host (Morimoto et al, 1996).…”
Section: Most Cases Of Rabies In the Unitedmentioning
confidence: 99%
“…Thus there is scant serologic information available on nonlethal exposures of bats that might help indicate whether there may be important species differences in rabies-virus-host interactions dictated by such factors as lifehistory traits, migratory behavior, and differences in virulence among virus variants. Furthermore, data about prevalence of antibodies to rabies virus are essentially lacking for the silver-haired bat (Lasionycteris noctivagans), a migratory tree bat and one of two species of bats commonly implicated in cryptic transmission of rabies virus to humans in the United States (Messenger et al, 2002;Franka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous infection may occur during skin exposure following a minute bite that escapes attention. The exact mode of viral entry from dermal nerves into the CNS by the bat rabies virus is unclear [16].…”
Section: Viral Transmissionmentioning
confidence: 99%
“…Mortality after untreated bites by rabid dogs ranges from 38 % to 57 % and depends on the severity and location of the wound, as well as on the presumed virus concentration in the saliva [16,156].…”
Section: Survival Following Rabies Encephalitismentioning
confidence: 99%